2020
DOI: 10.1038/s41598-020-66393-z
|View full text |Cite|
|
Sign up to set email alerts
|

Impediometric Electrochemical Sensor Based on The Inspiration of Carnation Italian Ringspot Virus Structure to Detect an Attommolar of miR

Abstract: electrochemical sensors are the tools to detect the accurate and sensitive miRs. there is the challenge to increase the power and sensitivity of the surface for the electrochemical sensor. We design a viruslike hallow structure of cuco 2 o 4 that it holds the large amounts of p19 protein by mimicking of inherent virus (Carnation italian ringspot virus) to detect 21mir with the limit of detection (LOD = 1aM). The electrochemical measurements are performed between the potentials at −0.3 V and +0.3 V with 1 mM [f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In the concentration range between 5.0 × 10 −13 M and 3.8 × 10 −8 M, the regression equation is ΔR/R = 6.2 × 10 −2 + 1.8 × 10 −2 Ln C, with a coefficient of determination R 2 = 0.9957 (N = 6). The detection limit (LOD) of MEL is calculated using the equation LOD = 3.3 SD/b, where (SD) and (b) are the standard deviation of the intercept and the slope of the calibration plot, respectively [ 42 ], and the calculated LOD is equal to 1.8 × 10 −12 M (at S/N = 3). Moreover, the reproducibility of the modified electrode GCE/PN–AuNPs–MB was assessed by the measurement of the response of three different modified electrodes, prepared with the same modification, to a 3 × 10 −12 M of MEL solution, by impedance spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…In the concentration range between 5.0 × 10 −13 M and 3.8 × 10 −8 M, the regression equation is ΔR/R = 6.2 × 10 −2 + 1.8 × 10 −2 Ln C, with a coefficient of determination R 2 = 0.9957 (N = 6). The detection limit (LOD) of MEL is calculated using the equation LOD = 3.3 SD/b, where (SD) and (b) are the standard deviation of the intercept and the slope of the calibration plot, respectively [ 42 ], and the calculated LOD is equal to 1.8 × 10 −12 M (at S/N = 3). Moreover, the reproducibility of the modified electrode GCE/PN–AuNPs–MB was assessed by the measurement of the response of three different modified electrodes, prepared with the same modification, to a 3 × 10 −12 M of MEL solution, by impedance spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Adding the SARS-CoV-2 Antigen on the MV-gal1/SCPE-GNP shows that the peak currents increased from 13.9 to 15.4 µA and the ΔEp decreased from 83 to 73 mV, due to covering the glycosylation bond by gal1 and glycan of spike of SARS-CoV-2. A recent study of Kajiyazdi was showed that covering the glycosylation bonds when lectin used as a synthetic receptor to identify the glycan on the tumor cells of AML disease 26 , 27 . Our results indicate the possible connection of the gal1 with NTD-domain (Glycan domain) of the SARS-CoV-2 Antigen by increasing the current peak, which it causes to the reduction of electrochemical exchanges with the [Fe(CN) 6 ] −3/−4 redox probe, too.…”
Section: Resultsmentioning
confidence: 99%
“…The bioreceptor-bioanalyte interaction may lead to the change in conductance of the electrolyte solution and can be leveraged as a biosensing signal for developing an impedimetric or conductometric biosensor [56]. The electrodes play a pivotal role in the performance of an electrochemical biosensor.…”
Section: Ace2-based Electrochemical Detection Of Sars-cov-2mentioning
confidence: 99%